2002
DOI: 10.1590/s0004-28032002000100006
|View full text |Cite
|
Sign up to set email alerts
|

Elevação da gama-glutamiltransferase sérica na hepatopatia esquistossomótica não se correlaciona com a carga parasitária e precede alterações ultra-sonográficas

Abstract: RESUMO -Racional -As alterações hepáticas constituem as mais importantes manifestações da esquistossomose mansônica. Não são conhecidos fatores que expliquem elevação sérica de enzimas indicadoras de colestase na forma hepatoesplênica da doença. Objetivo -Avaliar a correlação entre elevação da γ-glutamiltransferase sérica e a carga parasitária e alterações ultra-sonográficas em pacientes esquistossomóticos. Casuística e método -Foram avaliados 25 pacientes portadores da forma crônica pura da esquistossomose, q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
4
1
1
Order By: Relevance
“…5, in group of subjects with the disease, an increase in the level of AST, in relation to control group. Although an increase of ALT was not observed in this work, previous studies suggest that high parasite load is one of the mechanisms for elevation of ALT in schistosomiasis (Amaral et al 2002).…”
Section: Discussioncontrasting
confidence: 78%
“…5, in group of subjects with the disease, an increase in the level of AST, in relation to control group. Although an increase of ALT was not observed in this work, previous studies suggest that high parasite load is one of the mechanisms for elevation of ALT in schistosomiasis (Amaral et al 2002).…”
Section: Discussioncontrasting
confidence: 78%
“…Poderia ser questionado se a carga parasitária alteraria os níveis de GGT. No entanto, recentemente, AMARAL et al (2) demonstraram não haver correlação significativa entre a carga parasitária e os níveis séricos de GGT. A relação encontrada por esses autores entre GGT elevada e índice de protrombina elevado poderia sugerir que a GGT se alteraria em formas mais avançadas da doença e não como resultado de indução microssomal.…”
Section: Discussionunclassified
“…The most important event in schistosomiasis is the hepatic changes that occur in the definitive hosts (AMARAL et al, 2002), which are related to fibrosis (TAO et al, 2003). Other studies have shown that hepatic function only changes in more severe forms of the disease, with organomegalies and ascites, or in association with uncompensated hepatitis or cirrhosis (FAHIM et al, 2000;EL-SHAZLY et al, 2001).…”
Section: Introductionmentioning
confidence: 99%